Navigating the Impact of Remote Work Arrangement on the Employee Professional Growth and Development at the Workplace - Solanki, Kalpana (Archives of Business Research, 2024)
This research paper aims at exploring the impact of the of Remote Work on Employee Engagement, skill enhancement, Productivity and happiness in UAE based private and public sector employees. Remote work has been seen as a new way of working in the modern business after the Covid 19 Pandemic. This work arrangement is gaining popularity in many industries around the world specially middle east. This research will investigate the assumption that remote work has a wider impact on the employee’s engagement, skills, productivity and happiness level. The research concluded that all the 4 hypothesis were supported by the findings which indicate a positive relationship between the remote work arrangement and the Employee Engagement, skill enhancement, Productivity and happiness of the employees. The researcher has used quantitate as well as qualitative and quantitative measurements for testing the hypothesis including the surveys, interviews and Descriptive statistics including ANOVA, linear regression, and other techniques to obtain the results.